Stable High‐Conductivity Ethylenedioxythiophene Polymers via Borane‐Adduct Doping. (6th October 2022) - Mukhopadhyaya, Tushita; Lee, Taein D.; Ganley, Connor; Tanwar, Swati; Raj, Piyush; Li, Lulin; Song, Yunjia; Clancy, Paulette; Barman, Ishan; Thon, Susanna; Katz, Howard E.
Abstract: Efficient doping of polymer semiconductors is required for high conductivity and efficient thermoelectric performance. Lewis acids, e.g., B(C6 F5 )3, have been widely employed as dopants, but the mechanism is not fully understood. 1:1 "Wheland type" or zwitterionic complexes of B(C6 F5 )3 are created with small conjugated molecules 3, 6‐bis(5‐(7‐(5‐methylthiophen‐2‐yl)‐2, 3‐dihydrothieno[3, 4‐b][1, 4]dioxin‐5‐yl)thiophen‐2‐yl)‐2, 5‐dioctyl‐2, 5‐dihydropyrrolo[3, 4‐c]pyrrole‐1, 4‐dione [oligo_DPP(EDOT)2 ] and 3, 6‐bis(5''‐methyl‐[2, 2':5', 2''‐terthiophen]‐5‐yl)‐2, 5‐dioctyl‐2, 5‐dihydropyrrolo[3, 4‐c]pyrrole‐1, 4‐dione [oligo_DPP(Th)2 ]. Using a wide variety of experimental and computational approaches, the doping ability of these Wheland Complexes with B(C6 F5 )3 are characterized for five novel diketopyrrolopyrrole‐ethylenedioxythiophene (DPP‐EDOT)‐based conjugated polymers. The electrical properties are a strong function of the specific conjugated molecule constituting the adduct, rather than acidic protons generated via hydrolysis of B(C6 F5 )3, serving as the oxidant. It is highly probable that certain repeat units/segments form adduct structures in p ‐type conjugated polymers which act as intermediates for conjugated polymer doping. Electronic and optical properties are consistent with the increase in hole‐donating ability of polymers with their cumulative donor strengths. The doped film of polymer (DPP(EDOT)2 ‐(EDOT)2 ) exhibits exceptionally good thermal and air‐storage stability. The highest conductivities, ≈300 and ≈200 S cm −1, are achieved for DPP(EDOT)2 ‐(EDOT)2 doped with B(C6 F5 )3 and its Wheland complexes. Abstract : Lewis acids are p ‐dopants for polymers but the mechanism is not fully understood. Zwitterionic complexes of B(C6 F5 )3 with two conjugated molecules are investigated as models for the complex that Lewis acids can form with p ‐dopable polymers. The complexes are used to dope five electron‐rich polymers to high hole conductivity. The role of complexes is supported using multiple experimental and computational techniques.